Association Between Medication Adherence and Quality of Life Among Tuberculosis Patients: A Study at Permata Kuningan Hospital - Anwarudin, Wawang; Hanum, Salwa Diana; Marlindasari, Liska; Sya'bany, Anna Khalida; Azizah, Nur (Sciences of Pharmacy, 2026)
Tuberculosis (TB) remains a major global health concern, particularly in high-burden countries such as Indonesia. Although TB is curable, prolonged therapy, potential adverse effects, and social stigma may affect medication adherence and patients’ quality of life (QoL). Evaluating the association between adherence and QoL is important to support patient-centered TB management. This study aimed to examine the association between medication adherence and quality of life among tuberculosis patients at Permata Kuningan Hospital. A cross-sectional analytic study was conducted involving 62 TB patients selected through purposive sampling. Medication adherence was assessed using the Morisky Medication Adherence Scale (MMAS-8), and quality of life was measured using the EQ-5D-5L instrument. Data were analyzed using Spearman rank correlation. Most patients demonstrated high adherence (95.2%) and reported good quality of life (96.8%). Statistical analysis showed a significant positive correlation between medication adherence and quality of life (r = 0.384; p = 0.002), indicating that higher adherence was associated with better quality of life. These findings suggest a significant association between medication adherence and quality of life among TB patients. Strategies to support adherence, including education, counseling, and monitoring, may be considered as part of comprehensive TB care to optimize patient-centered outcomes.